ASAS TRANSPARANSI DALAM PROSES PENGANGKATAN PERANGKAT NAGARI - Ilosa, Abdiana; Sukri, Saipul Al; Rudiadi, Rudiadi (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2021)
Village officials have a great obligation and responsibility to help the Village Head carry out his duties, obligations and provide the best service to the community. The selection of the right village officials will support the implementation of these tasks and obligations. Considering the position of the village apparatus that is so important, the recruitment process, procedures and requirements that are appropriate for the candidate village apparatus are needed.The purpose of this study was to determine the implementation and constraints of the principle of transparency in the appointment of the sontang cubadak Nagari village in Pasaman, West Sumatra. Data collection in this study used interview techniques (key informants). While the types and sources of data used in this study are primary and secondary data. From there the data is then analyzed in a qualitative descriptive way. The results of this study provide evidence that transparency does not occur in the process of appointing Sontang Cubadak Nagari. This happens because of the lack of transparency in the selection, recruitment of candidates for the device. This is evidenced from the many people of Sontang Cubadak village who do not know the process and only know the results of the appointment. In addition, the supervision of the sub-district and the lack of good communication between the Nagari government and the community also caused the failure of the appointment of the Sontang Cubadak village government apparatus.Â Keyword: Regional Autonomy, Transparency Principle, Nagariâ€™s Officer